Initial Experience With the New York State Breast Density Inform Law at a Community‐Based Breast Center. (1st June 2015) - Destounis, Stamatia; Arieno, Andrea; Morgan, Renee
Abstract : Objectives: The purpose of this study was to review our initial experience with the New York State breast density inform law (New York public health law, S2404‐C) at our outpatient breast center. We sought to review the findings in patients returning for screening breast sonography after a screening mammogram revealed heterogeneously dense or extremely dense breast tissue. Methods: From January 1, 2013, through May 31, 2014, 102, 841 patients who underwent screening mammography were seen at our institution. Of these, 35, 153 were determined to have heterogeneously dense breast tissue, and 11, 864 were determined to have extremely dense breast tissue. Due to the New York State breast density inform law, these 47, 017 patients were notified of their breast density, with 935 patients (2%) returning for 971 screening breast sonographic examinations. Results: Heterogeneously dense breast tissue was noted in 66% of the patients (619), and extremely dense breast tissue was noted in 34% (316). Thirty‐one percent of the patients (290) reported no additional risk factors; 68% (635) presented with 1 or more additional risk factors; and 1% (10) were adopted, and the risk status could not be assessed. Twenty‐five procedures (2.6%) were performed after screening breast sonography, resulting in 22 benign findings, 1 atypical finding, and 2 malignancies. The overall positive predictive value was 8% (2 of 25), and the overall cancer detection rate was 2.1 per 1000 (2 of 935). Conclusions: Handheld screening breast sonography performed in women with dense breast tissue can aid in the detection of otherwise occult breast cancer, as we found 2 cancers in the study population, with an overall positive predictive value of 8%. The addition of screening sonography in this cohort did lead to an increase in minimally invasive procedures in 2.6%.